Identifying fossil rabbit warrens: Insights from a taphonomical analysis of a modern warren. (December 2016) - Pelletier, Maxime; Brugal, Jean-Philip; Cochard, David; Lenoble, Arnaud; Mallye, Jean-Baptiste; Royer, Aurélien
Abstract: The European rabbit is a small burrowing mammal that is particularly abundant in Western Europe since the Pleistocene and introduced around the world over the last few centuries. Rabbit bones are regularly recovered from archaeological and palaeontological sites; however, demonstrating their contemporaneity with associated material is often difficult. Additionally, determining the origin of rabbit remains in fossil sites is equally problematic due to the lack of reference collections for natural accumulations. In order to address these issues, we excavated a modern rabbit warren in southwestern France using modern archaeological field methods and techniques. The bone accumulation was analysed using a taphonomic approach in order to determine the most relevant criteria for identifying fossil warrens. The assemblage is heavily fragmented and dominated by individuals less than three months old and, unlike what could be expected, no preserved anatomical connections were documented. Bone concentration is low and connected to occupation duration. Taken together, the criteria we identify aide in better identifying fossil warrens in fossil sites as well as evaluate the integrity of the deposits. Finally, our results also add precision to environmental, biostratigraphic and palaeoethnographic interpretations. Highlights: First modern referential for natural mortality in the rabbit's habitat Archaeological excavation of a modern rabbit warren Taphonomic characterization of an attritional mortality accumulation Highlighting bioturbation processes linked to burrowings within an archaeological site